Global indios: the indigenous struggle for justice in sixteenth-century Spain - Van Deusen, Nancy E. (Narrating native histories, 2015)
All the world in a village: Carmona -- Crossing the Atlantic and entering households -- Small victories: Gregorio López and the reforms of the 1540s -- Into the courtroom -- Narratives of territorial belonging, just war, and ransom -- Identifying indios -- Transimperial indios